Binding behavior between transforming-growth-factor-beta1 and its receptor reconstituted in biomimetic membranes - Shin, Gounhanul (2023)
Transforming growth factor β1 (TGF-β1) is critical to cell differentiation, proliferation, and apoptosis. It is important to understand the binding affinity between TGF-β1 and its receptors. In this study, their binding force was measured using an atomic force microscope. Significant adhesion was induced by the interaction between the TGF-β1 immobilized on the tip and its receptor reconstituted in the bilayer. Rupture and adhesive failure occurred at a specific force around 0.4~0.5 nN. The relationship of the force to loading rate was used to estimate the displacement where the rupture occurred. The binding was also monitored in real time with surface plasmon resonance (SPR) and interpreted with kinetics to acquire the rate constant. Using the Langmuir adsorption, the SPR data were analyzed to estimate equilibrium and association constants to be approximately 107 M-1 and 106 M-1 s-1. These results indicated that the natural release of the binding seldom occurred. Furthermore, the degree of binding dissociation, confirmed by the rupture interpretation, supported that the reverse of the binding hardly happened.